A comprehensive study on the factors affecting near-nozzle spray dynamics of multi-hole GDI injectors. (15th February 2017) - Li, Tianyun; Moon, Seoksu; Sato, Kiyotaka; Yokohata, Hideaki
Highlights: Near-nozzle spray dynamics were studied using X-ray phase-contrast imaging. Effects of injection parameters on near-nozzle spray dynamics were studied. Effects of fuel viscosity and surface tension on spray dynamics were minor. Near-nozzle spray dynamics can be scaled by introducing a characteristic distance. The scaled dynamic path showed a linear decrease different from that of gas jets. Abstract: In order to improve the engine thermal efficiency with reduced emissions, substantial studies have been carried out to investigate the factors affecting the fuel spray characteristics such as nozzle geometry, fuel property, and injection and ambient conditions. However, most of the previous studies have focused on the macroscopic structures of the fuel sprays, but detailed structures of internal spray dynamics have not been thoroughly investigated, especially in the near-nozzle region. In this study, the effects of critical injection parameters such as injection pressure, ambient density, fuel, nozzle hole diameter and length on the near-nozzle spray dynamics of multi-hole gasoline-direct-injection injectors were investigated using X-ray phase-contrast imaging and visible light imaging. Then, the scaling potential of the near-nozzle spray dynamic structure under various injection parameters was surveyed based on the gas jet theory. The results showed that the density ratio of the fuel and surrounding gas and spray angle are the governing factors of the near-nozzle spray dynamic structure. By introducing the governing factors as the scaling variables, the near-nozzle spray dynamic structure under various injection parameters can be scaled with near 90% correlation performance. However, the scaled dynamic path in the near-nozzle region is different with that of the gas jets that requires modifications of conventional gas-jet-based dynamics models for application to the near-nozzle region.